Management of Systemic Sclerosis Patients in the COVID-19 Era: The Experience of an Expert Specialist Reference Center. Issue 15 (March 2021) - Spinella, Amelia; Magnani, Luca; De Pinto, Marco; Marvisi, Chiara; Parenti, Luca; Bajocchi, Gianluigi; Salvarani, Carlo; Mascia, Maria Teresa; Giuggioli, Dilia
Objective: COVID-19 pandemic represents a serious health emergency that severely compromised our Public Health system, resulting in a rapid and forced reorganization and involved the management of chronic diseases too. The Scleroderma Unit of Modena and Reggio Emilia follows more than 600 patients suffering from systemic sclerosis (SSc) and recently became the referral center (HUB) in Emilia-Romagna for this rare connective tissue disease. The aim of the present study was to evaluate the extent by which the lockdown and the pandemic has impacted the activity of admissions to Scleroderma Unit of Modena and Reggio Emilia. Methods: Our daily clinical activity is characterized by outpatient visits, videocapillaroscopy exam, ulcers treatment, therapeutic infusions in day hospital regimen, multidisciplinary visits following our dedicated SSc care pathway, and clinical trials. Our activity has been quickly rescheduled to ensure the proper assistance to our SSc patients during the COVID-19 pressure. Results: The use of telemedicine has certainly assured a robust continuity of health care. Furthermore, telephone pre-triage, nurse/medical triage, proper physical distancing and use of PPE/DPI allowed us to re-organize and continue SSc daily activity. Specifically, therapeutic infusions in day hospital regimen and outpatient visits, including ulcers treatment, was guaranteed and maximized. Conclusion: The management of scleroderma patients by an expert specialist reference center is crucial in order to ensure continuity of care and pursue the best SSc practice.